Pedagogía en valores y su incidencia en la formación de los niños y niñas del quinto año de educación general básica de la Escuela General Julio Alberto Amores Tovar en el período lectivo 2016-2017 - Morocho Saltos, Katherine Liseth (2017)
The crisis of values in classrooms is an institutional problem that affects the learning and discipline of students, through observation and previous application of a survey was detected the need to carry out the project on Pedagogy in values in children And children of the fifth year of the General Basic General Education School Julio Alberto Amores Tovar, having as general objective the strengthening of the practice of values focusing on the improvement of academic performance and disciplinary conduct, contributing to the integral formation of the student, through the Elaboration and socialization of a methodological guide using the lúdico-creative method, the same one that consists of a compilation of contents, activities and scientific studies emitted by several authors that treat the subject of a very effective way, because in the educational institutions Is failing to practice such as the lack of solidarity, respect, responsibility, honesty, punctuality and more, being a fundamental basis in the academic training of people. A workshop was held where the activities had the purpose of raising awareness about the work that the entire educational community should carry out for their own benefit, with research having a social pedagogical impact that was facilitated to the attendees, benefiting approximately one hundred and fifty people.